2008
DOI: 10.1080/17483100701343475
|View full text |Cite
|
Sign up to set email alerts
|

MobileASL: Intelligibility of sign language video over mobile phones

Abstract: For Deaf people, access to the mobile telephone network in the United States is currently limited to text messaging, forcing communication in English as opposed to American Sign Language (ASL), the preferred language. Because ASL is a visual language, mobile video phones have the potential to give Deaf people access to real-time mobile communication in their preferred language. However, even today's best video compression techniques can not yield intelligible ASL at limited cell phone network bandwidths. Motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 6 publications
0
44
0
1
Order By: Relevance
“…One would think that ASL, which is a temporal visual language, would require video communication to be transmitted at high frame rates; however, we discovered this is not the case at low bitrates. The preference of viewing ASL video at 10 fps over 15 fps was also discovered in earlier ASL video communication research conducted by Cavender et al [4] However, their findings only reported a slight but significant main effect that frame rate influenced video intelligibility. Our results strongly affirm that ASL video intelligibility peaks at 10 fps across all bitrates.…”
Section: Frame Rate and Bitratementioning
confidence: 54%
See 3 more Smart Citations
“…One would think that ASL, which is a temporal visual language, would require video communication to be transmitted at high frame rates; however, we discovered this is not the case at low bitrates. The preference of viewing ASL video at 10 fps over 15 fps was also discovered in earlier ASL video communication research conducted by Cavender et al [4] However, their findings only reported a slight but significant main effect that frame rate influenced video intelligibility. Our results strongly affirm that ASL video intelligibility peaks at 10 fps across all bitrates.…”
Section: Frame Rate and Bitratementioning
confidence: 54%
“…One fps was selected to achieve a sufficiently low frame rate to observe that intelligibility clearly suffered. Prior work investigating the impact of frame rate on perceived video quality acknowledged not selecting a low enough frame rate to explore in their study [4,16]. Although transmitting video at 1 fps is not ideal for ASL conversations, we did notice that transmitting video at 1 fps and 15 kbps, which is the lowest bitrate, received the highest mean Likert score across all bitrates at 1 fps.…”
Section: Frame Rate and Bitratementioning
confidence: 65%
See 2 more Smart Citations
“…Cavender et al [6] conducted a laboratory study evaluating perceived video intelligibility of pre-recorded ASL videos transmitted at two frame rates (10 and 15 fps), three bit rates (15,20, and 25 kbps), and three region-of-interest (ROI) encoding levels (0, -6, and -12 ROI). They discovered a frame rate preference of 10 fps for viewing ASL video at a fixed bit rate.…”
Section: Mobileasl Projectmentioning
confidence: 99%